The Relationship Between Level of Knowledge About Early Mobilization with Pain Intensity of Post Laparotomy Patients - Danik Sri Widayati; Ach. Dafir Firdaus; Feriana Ira Handian (The Journal of Palembang Nursing Studies, 2022)
Background: Laparotomy surgery cause severe pain intensity immediately post-surgery. Sufficient knowledge is predicted to be the patient’s provision to determine effective pain management through early mobilization. Purpose: The study aimed to determine the relationship between early mobilization knowledge and pain intensity on postoperative laparotomy patients. Methods: Cross-sectional study with 41 respondents were treated in the COVID-19 ward at Dr. Saiful Anwar Hospital. Data were collected by early mobilization knowledge questionnaire and Verbal Response Scale (VRS). Data were analyzed using the Spearman rho test with a significance value ? = 0.05. Results: The study showed 20 respondents (48.8%) have good knowledge of early mobilization. Of the amount, 25 respondents (61%) felt mild pain post laparotomy surgery. Statistical tests showed a significant relationship between knowledge of early mobilization and pain intensity (p = 0.046). Conclusions: Early mobilization knowledge correlates with pain intensity. Study results suggest for nurses to increase early mobilization education in post-laparotomy patients.